Judicial Review of Administrative Silence - Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Administrative silence is a situation in which the competent authority, within the statutory deadline, has not issued an administrative act at the request of the party. In the case of administrative silence, given the fact that the citizens are unable to protect their rights and legal interests without an administrative act, they are provided with legal protection. In this case, the same legal relationship is created, directly on the basis of the statute, as in the situation in which the party’s request is rejected. This means that the party may, under the conditions prescribed by the statute, initiate the procedure of judicial review of administrative silence. In the paper, the author explains the conditions under which the judicial review of administrative silence can be initiated and the role of the court in this judicial procedure.